Japan : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2006)
The Report on the Observance of Standards and Codes data module provides an assessment of Japan's macroeconomic statistics against the Special Data Dissemination Standard, complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework, July 2003 version. The assessment reveals that the data-producing agencies in Japan adhere to the principle of objectivity in the collection, processing, and dissemination of statistics. They demonstrate professionalism and are transparent in their policies and practices. Data are protected by strict measures of confidentiality throughout the data-producing agencies.